Emprego de derivados celulósicos esterificados na imobilização da fosfolipase Lecitase® Ultra - Rodrigues, Lucas Pires (2018)
Enzymatic processes stand out from other catalytic processes due to high selectivity, enzyme activity, efficiency and milder experimental conditions, such as working temperatures close to ambient temperature, and acidic or basic media with low concentration. However, the free enzymes are quite unstable in the reactional environment and difficult to recover. In view of this, immobilization of the enzymes in polymeric supports can provide a stability necessary for the accomplishment of several catalytic cycles. In this work, esterified cellulosic matrices - cellulose diacetate (CDA), cellulose triacetate (CTA) and cellulose acetate butyrate (CAB) - as well as Kraft pulp cellulose (PCEL) and microcrystalline cellulose (MCEL) were tested for immobilization by physical adsorption of the comercial phospholipase Lecitase® Ultra (LU). The cellulosic matrices were evaluated in relation to the presence of the functional groups by infrared spectroscopy, where it is observed that the CTA has a higher degree of substitution due to the low intensity of the band indicating the presence of hydroxyls and the high intensity of the carbonyl band. This presented higher retention of enzymatic activity in relation to the other derivatives. The CTA was subjected to optimization of the immobilization methodology by Central Rotational Composite Design (CRCD), with the objective of investigating the concentration of LU in the immobilization buffer solution, pH and temperature and the interaction between these factors. Multiple regressions were made from the experimental data obtained in the CRCD matrix and response surfaces were constructed for immobilization yield and enzyme concentration in the bioactive derivative obtained by immobilization. A high enzymatic loading on the surface of the CTA was identified as an optimal working region, a pH lower than 4.00, temperatures higher than 40ºC and a concentration of LU in the buffer solution greater than 350 mg of protein/g support. The highest enzyme concentration on CTA was found at a concentration of LU in the buffer of 370.94 mg protein/g support, 45.2°C and pH of 1.95, obtaining a bioactive derivative of 251.41 mg protein/g support, experimentally. This optimized bioactive derivative was used to deguminate soybean oil, allowing the removal of the gums and leading to an increase in acidity due to the hydrolysis of the triglycerides in this condition showing that both the free and immobilized enzyme has high enzymatic activity. However, the enzyme immobilizes promotes less hydrolysis, which may be related to a possible modulation of its activity, in order to reduce its hydrolytic action on triglyceride fatty acids, identified by the acidity index of crude and degummed soybean oil. The results showed that the use of TAC as support for adsorption of LU proved promising, due to the high capacity of enzymatic retention and maintenance of the catalytic activity of the enzyme after immobilization.